2012
DOI: 10.1021/la301181b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Environmentally Responsive Cationic Liposome–DNA Complexes with a Reducible Lipid Linker

Abstract: Environmentally responsive materials, i.e., materials that respond to changes in their environment with a change in their properties or structure, are attracting an increasing amount of interest. We recently designed and synthesized a series of cleavable multivalent lipids (CMVLn, with n = 2 to 5 the number of positive headgroup charges at full protonation) with a disulfide bond in the linker between cationic headgroup and hydrophobic tails. The self-assembled complexes of the CMVLs and DNA are a prototypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…CD measurements (Figure S11), in addition showed that the DNA segments in dsCon primarily took the more compact B‐form, unlike dsDNA of the same sequences, which in control studies formed mostly A‐type helix structures, as typically observed for short G‐C‐rich sequences . Taken together, our results indicate the formation of multi‐lamellar spherical architectures (Figure f, inset), as was previously observed for related assemblies formed by Janus soft‐matter building blocks, such as lipid‐DNA molecules …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…CD measurements (Figure S11), in addition showed that the DNA segments in dsCon primarily took the more compact B‐form, unlike dsDNA of the same sequences, which in control studies formed mostly A‐type helix structures, as typically observed for short G‐C‐rich sequences . Taken together, our results indicate the formation of multi‐lamellar spherical architectures (Figure f, inset), as was previously observed for related assemblies formed by Janus soft‐matter building blocks, such as lipid‐DNA molecules …”
Section: Resultssupporting
confidence: 84%
“…[11b] Ta ken together,o ur resultsi ndicate the formation of multi-lamellar spherical architectures (Figure 4f,i nset), as was previously observed for related assemblies formed by Janus soft-matter building blocks, [12] such as lipid-DNA molecules. [13] Several recently published works have described the self-assembly of NA-pepc onjugatesi nto vesicle or fibril-like architectures. In such studies,s cientist have characterized assemblies formed by NA moieties attached to either short peptides [14] or to positively charged peptides that strongly interact intramolecularlyw ith the NA segments.…”
Section: Resultsmentioning
confidence: 99%
“…208 Moreover, the same group showed via small-angle and wide-angle X-ray scattering (SAXS and WAXS) a change in morphology of CMVL4 118f/DOPC-DNA complexes from L α C lamellar to a loosely organized phase upon exposure to reducing agents such as DTT and glutathione (GSH).The hydrophobic part rearranged into a tilted chain-ordered L β phase upon incubation at 37 o C, while the cationic part formed DNA bundles. Lipoplexes of 118h congener formulated in the same conditions as 118f were insensitive to reducing agents, proving that disulfide reduction of 118f is responsible for the change in the morphology 209. Malhotra et al introduced a new series of multivalent oligoglycerol amphiphilic dendrons119a-119d for gene delivery.…”
mentioning
confidence: 99%
“…3), the size sharply reach a maximum followed by a decrease at higher positive charge ratios which has been attributed to the re-entrant condensation effect [146]. [45,54,60,62,75,93,113] or multivalent cationic lipids [63,65,67,147]; (b) polyplexes formed by pDNA with cationic polymers [148,149] or polycations [141]; (c) lipoplexes formed by siRNA with GCLs [114,150,151] or MVCLs [72,152] mediated by a helper lipid as DOPE, MOG or DOPC; and (d) polyplexes formed by siRNA with cationic polymers [153]. Fig.…”
Section: Size Structure and Morphologymentioning
confidence: 99%